Bioelectricity Generation from Bamboo Leaves Waste in a Double Chambered Microbial Fuel Cell - SAHARI, SITI KUDNIE; BUTIT, AMIR MAINA; NGAINI, ZAINAB; YANUAR ZULARDIANSYAH ARIEF, YANUAR ZULARDIANSYAH ARIEF; KURYATI KIPLI, KURYATI KIPLI; MARTIN ANYI, MARTIN ANYI; ASMAHANI AWANG, ASMAHANI AWANG; MUHAMMAD KASHIF, MUHAMMAD KASHIF; MOHAMAD RUSOP MAHMOOD, MOHAMAD RUSOP MAHMOOD; ZAIDI EMBONG, ZAIDI EMBONG; LILIK HASANAH, LILIK HASANAH; ABDUL RAHMAN KRAM, ABDUL RAHMAN KRAM; et al. (2023)
This study investigated the utilization of bamboo leaf waste and two varieties of bacterial sources, chicken manure and effective microorganism, in a microbial fuel cell (MFC) at three substrate concentrations (40 g/liter, 80 g/liter, and 160 g/liter). The primary objective was to investigate the kinetics of bacterial growth at various substrate concentrations in the MFC, as well as the effect of light conditions and pH on MFC power generation. The MFC had dual chambers with graphite electrodes serving as the cathode and anode. Within 72 h, the highest power density of 90.05 mV was attained using the highest substrate concentration of bamboo leaf waste and chicken manure during the logarithmic growth phase, albeit with a shorter duration. The longest sustained phase of bacterial activity was observed during the stationary phase, at the highest substrate concentration of 160 g/liter, followed by 80 g/liter and 40 g/liter. These results indicate that the logarithmic phase is the optimal time for bacterial activity in the MFC. However, attaining long-term stability in power generation in the logarithmic phase requires careful parameter optimization.